Application of Articulate Storyline Media to Improve the Mathematical Problem Solving Ability of Grade 1 Students of SD Muhammadiyah 14 Surabaya - Feby Rahmania Budiyani; Deni Adi Putra; Kunti Dian Ayu Afiani (Indonesian Journal of Primary Education, 2025)
The purpose of this study is to analyze the application of Articulate Storyline media to improve the mathematical problem-solving ability and learning outcomes of grade 1 students of SD Muhammadiyah 14 Surabaya. The method uses classroom action research (PTK) with a cycle model. The subject is grade 1 students. The data collection technique uses observation, tests in the form of story questions and documentation. The data is then analyzed descriptively. The results reflect that there is an improvement in mathematical problem-solving skills and learning outcomes of students through the application of Articulate Storyline media. This is evidenced by the students' initial ability to solve mathematical problems reaching a score of 47, in the first cycle it became 78, and in the second cycle it became 95. Meanwhile, the average increase in learning outcomes was 66.9 in the pre-cycle stage, to 78.1 in the first cycle and 88.7 in the second cycle